Exploring the Impact of Land and Building Tax (PBB) on Original Regional Income (PAD): A Study in Regional Economics and Fiscal Governance - Adiwilaga Putra; Ananda Mahiswara (Institute of Accounting Research and Novation (IARN), 2024)
This research investigates the relationship between Land and Building Tax (PBB) and Original Regional Income (PAD), aiming to provide empirical insights into the impact of property taxation on regional economic dynamics. Utilizing a comprehensive methodology that integrates quantitative analysis, qualitative interpretation, and literature review, the study examines correlations, causal effects, and influencing factors shaping the relationship between PBB and PAD. The findings reveal a significant positive correlation between PBB revenue and PAD, highlighting the crucial role of property taxation as a revenue source for financing local governance, infrastructure projects, and community development initiatives within regions. Moreover, the analysis identifies various causal pathways through which PBB influences PAD, including direct revenue generation, indirect economic effects, and policy interactions. Factors such as economic conditions, property market dynamics, governance structures, policy interventions, and socio-demographic trends are identified as influencing the relationship between PBB and PAD. The implications of these findings for policy and practice are discussed, emphasizing the importance of progressive tax policies, targeted exemptions, investment in tax administration systems, and transparency and accountability in property tax management. Overall, this research contributes to the understanding of property tax policy, fiscal decentralization, and regional governance, offering insights for policymakers, practitioners, and researchers seeking to promote inclusive and sustainable development within regions worldwide.